2016
DOI: 10.1902/jop.2016.150500
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Clinical and Radiographic Study of Alveolar Ridge Preservation Combining Freeze‐Dried Bone Allograft With Two Xenogeneic Collagen Matrices

Abstract: Both xenogeneic collagen matrices combined with FDBA were effective in maintaining soft tissues and minimizing ridge resorption in all dimensions after ARP. BPT was an important determinant for amount of change in crestal GT and ridge width.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 38 publications
(131 reference statements)
2
30
0
2
Order By: Relevance
“…The hard tissue dimensional changes that we report in this study resemble changes reported in recent studies of tooth extraction and ridge preservation by others that used either an autogenous soft tissue (free gingival graft) punch (6–8 mm in diameter) or a punch modification of the CM with the same diameter (similar to the CMS) to cover the bone graft (Jung et al., ; Schneider et al., ). Those changes are also consistent with the results observed in a recent study that performed ARP with a combination of FDBA and CM or an extracellular collagen matrix as barriers (Parashis et al., ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The hard tissue dimensional changes that we report in this study resemble changes reported in recent studies of tooth extraction and ridge preservation by others that used either an autogenous soft tissue (free gingival graft) punch (6–8 mm in diameter) or a punch modification of the CM with the same diameter (similar to the CMS) to cover the bone graft (Jung et al., ; Schneider et al., ). Those changes are also consistent with the results observed in a recent study that performed ARP with a combination of FDBA and CM or an extracellular collagen matrix as barriers (Parashis et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…However, other authors did not report any significant differences with or without flap elevation (Araujo & Lindhe, ) and a recent systematic review found that flap elevation had a beneficial effect on preservation of buccal alveolar bone height (Avila‐Ortiz, Elangovan, Kramer, Blanchette, & Dawson, ). Although it is suggested that wound dehiscence and membrane exposure could result in infection and lack of bone formation, recent studies show that the intentional exposure of bioabsorbable barriers does not seem to adversely affect ARP procedures (Barone et al., ; Jung et al., ; Parashis et al., ). We observed no adverse effects in this study where the barriers were left exposed to the oral cavity, and sutures were used primarily to stabilize the barriers in place.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations